The Power to Dissolve the People’s National Assembly in the Light of the Constitutional Amendment of 2020 - Tebina, Hakim (Journal of Legal Studies and Researches, 2023)
The constitutional amendment of 2020 included various controls related to the dissolution of People’s National Assembly, especially by obligating; the re-conducting of legislative elections within the specified time, preventing the delegation of the power of dissolution and the inability to dissolve in exceptional cases.